An identity involving automorphisms of prime rings inspired by Posner's theorem. Issue 3 (4th May 2018) - Ashraf, Mohammad; Pary, Sajad Ahmad
ABSTRACT: Let be a prime ring with centre, a non-zero Lie ideal of, and σ a non-trivial automorphism of such that for all . If, then it is shown that satisfies, the standard identity in four variables.